Difference in Coronary Angiographic Patterns of Diabetic and Non-Diabetic Patients Presenting with STEMI to SGTH Saidu Sharif Swat - Ahmad, Sohail; Hafiz Ur Rahman; Badshah, Umar; Abdul Latif; Khan, Liaqat Ullah (Indus Journal of Bioscience Research, 2025)
Objective: To examine the coronary angiographic patterns in diabetic and non-diabetic patients presenting with ST-elevation myocardial infarction (STEMI) at SGTH Saidu Sharif, Swat. It aimed to compare the severity and complexity of coronary artery disease in both groups. Methodology: This prospective study was conducted between 1st March 2025, and 31st May, 2025, at the Department of Cardiology, Saidu Group of Teaching Hospitals, Saidu Sharif Swat. A total of 220 patients, 110 diabetic and 110 non-diabetic, were included. Data was collected from patient records, focusing on age, comorbidities, angiographic patterns, lesion severity, and coronary artery involvement. Statistical analysis was performed using chi-square tests to compare the groups. Results: The study found no significant differences between diabetic and non-diabetic patients in terms of angiographic patterns (p = 0.96) and lesion severity (p = 0.96). Diabetic patients had a mean age of 48.1 years (±16.4), while non-diabetic patients had a mean age of 44.2 years (±17.5). Hypertension was more prevalent in diabetic patients (87%) compared to non-diabetic patients (60%). In terms of lesion severity, 36.9% of diabetic patients had mild lesions, 28.5% had moderate lesions, and 34.6% had severe lesions. Conclusion: The study concluded that there were no significant angiographic differences between diabetic and non-diabetic patients with STEMI. Despite the known association between diabetes and more severe coronary artery disease, further research is required to explore additional clinical factors that may influence coronary artery involvement in diabetic patients.